Implementation of Digital E-Procurement in the Sharia Banking Ecosystem - Nurbaidah, Siti Umi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines how e-Procurement implementation supports cost efficiency, strengthens sharia compliance, and addresses adoption challenges in Indonesian Islamic banks. Using a qualitative case study approach based on regulations, DSN-MUI fatwas, annual reports, and technological practices, the research highlights a conceptual gap in integrating maqāṣid al-sharī‘ah within digital procurement. Findings indicate that procurement digitization lowers transaction costs and enhances sharia compliance through digital hisbah-based audits. The study’s novelty lies in proposing a techno-fiqh integrative model that aligns economic efficiency with maqāṣid principles. Practical implications include recommendations for regulatory refinement, digital sharia auditing, and blockchain-based contract validation.